Analysis of Primary Metabolite Content in Shallot Bulbs from Bantul and Sragen Basic Steps for Plant Breeding - Hardian Ningsih; Herlina Mega Puspitasari; Zainal Arifin; Amelga Via Playnia Mars (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2025)
Shallots (Allium cepa L. var. aggregatum) are strategic horticultural commodities rich in primary metabolite compounds that are important for nutritional value and quality of harvest. This study aims to analyze and compare the primary metabolite content in shallot bulbs from Bantul (Special Region of Yogyakarta) and Sragen (Central Java) using the proximate test method. The parameters tested include water content (thermogravimetric method), ash/minerals (dry method), fat (Soxhlet method), protein (Kjeldahl method), and carbohydrates (by different). Analysis was carried out on fresh samples from both areas representing the main production centers. The results showed differences in the composition of primary metabolites between the two samples. This difference indicates the influence of environmental factors and cultivation techniques on the nutritional profile of shallot bulbs. These findings are expected to serve as a basis for selecting cultivation sites based on nutritional quality, developing processed products that match the nutritional characteristics of the raw materials and are expected to serve as a basic step in plant breeding.